2008
DOI: 10.1117/12.777208
|View full text |Cite
|
Sign up to set email alerts
|

Rendezvous lidar sensor system for terminal rendezvous, capture, and berthing to the International Space Station

Abstract: The Rendezvous Lidar System (RLS), a high-performance scanning time-of-flight lidar jointly developed by MDA and Optech, was employed successfully during the XSS-11 spacecraft's 23-month mission. Ongoing development of the RLS mission software has resulted in an integrated pose functionality suited to safety-critical applications, specifically the terminal rendezvous of a visiting vehicle with the International Space Station (ISS). This integrated pose capability extends the contribution of the lidar from long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Lidar has been used extensively during the past few years for in-orbit space shuttle inspection (Gregoris et al, 2004) and, more recently, for autonomous satellite rendezvous (Allen et al, 2008). The use of lidar as a vision system for long-range rover navigation has also received considerable attention (Dupuis et al, 2008).…”
Section: Background and Related Workmentioning
confidence: 99%
“…Lidar has been used extensively during the past few years for in-orbit space shuttle inspection (Gregoris et al, 2004) and, more recently, for autonomous satellite rendezvous (Allen et al, 2008). The use of lidar as a vision system for long-range rover navigation has also received considerable attention (Dupuis et al, 2008).…”
Section: Background and Related Workmentioning
confidence: 99%
“…From the researches that have been done, it can be concluded that the visual sampling and image processing are time-consuming, and the visual sampling frequency is usually 5 Hz, 16,17 while the robot control frequency is 500 Hz or higher. One of the methods to coordinate the frequencies is to apply the interpolation method to the visual servoing process.…”
Section: The General Scheme Of Space Robot Controlmentioning
confidence: 99%
“…5 this system is based on a fiber laser with radiation pulse width 1 ns, operating at a repetition rate from 8 to 10 kHz. The scanning over two coordinates was carried out by two independently controlled mirrors in the range 10°.…”
Section: Laser Systems For Spacecraft Rendezvous and Dockingmentioning
confidence: 99%